Enhancing Collaboration and Problem-Solving Skills: The Role of Blended Project-Based Learning - Anisa Nur Intan; Rahma Diani; Yani Suryani (Universitas Lambung Mangkurat, 2025)
The ability to collaborate and solve problems is essential for students facing 21st-century learning challenges. However, these skills are often underdeveloped in conventional classroom settings. This study aims to investigate the effect of blended project-based learning (BPjBL) on students’ collaboration and problem-solving skills. A quasi-experimental method was used. The research was conducted at SMA Negeri 1 Sungkai Utara, North Lampung Regency, during the 2023/2024 academic year. The population comprised five science classes (XI IPA 1–XI IPA 5), with a total sample of 55 students selected through cluster random sampling. Class XI IPA 2 (28 students) served as the experimental group, while class XI IPA 3 (27 students) served as the control group. Data were collected using a problem-solving ability test, collaboration skill observation sheets, and learning implementation instruments. The results showed that the BPjBL model had a significant effect on students’ collaboration skills (p = 0.005 < 0.05) and problem-solving abilities (p = 0.007 < 0.05). These findings indicate that integrating blended and project-based approaches can meaningfully enhance key 21st-century competencies. This study contributes to the growing body of evidence supporting active learning models and suggests that BPjBL can be effectively implemented in senior high school. These results suggest that BPjBL can be a useful teaching method for promoting critical 21st-century skills and should be considered in curriculum development for science education.